PENGARUH REKRUTMEN, SELEKSI, DAN PELATIHAN TERHADAP KINEJA KARYAWAN PT QES INDONESIA - Sarpan, Sarpan; Alam, Ilham Kudratul; Awaludin, Muryan (JURNAL MITRA MANAJEMEN, 2024)
The aim of this research is to analyze the relationship between the influence of recruitment, selection and training of PT QES Indonesia employees. The number of samples was 32 people. This research uses quantitative methods with probability sampling techniques (random samples), and data analysis tools using the SPSS version 20 program. The results of the partial analysis of recruitment on employee performance show that there is no significant relationship because tcount 0.174 is smaller than ttable 2.037 and the significance is >0.05. The results of the partial selection analysis of employee performance show that there is no significant relationship because tcount 0.496 is smaller than ttable 2.037 and the significance is >0.05. The results of the partial analysis of training on employee performance show that there is no significant relationship because tcount 0.205 is smaller than ttableÂ¬ 2.037 and the significance is >0.05. The results of simultaneous analysis of recruitment, selection and training on employee performance show that there is no significant relationship because the fcount of 0.151 is smaller than the ftable of 2.947, with significance >0.05Â Keyword: Recruitment, Selection, Training, Employee Performance